Behavior of Rail Ballast Layer Using Mortar Foam with LISA-FEA - Aco Wahyudi Efendi; Yahya Do; Natriya Faisal Rachman (Politeknik Perkeretaapian Indonesia Madiun, 2022)
In the development of railroads, geosynthetics can be introduced in or under the stabilizer layer or sub ballast, foam mortar has become one of the trends in the construction sector in replacing the foundation layer as an excellent alternative. The researcher conducted a comparative analysis on railroad ballast by using a substitute for conventional railroad ballast material, namely granular material using mortar foam, conducting research on the stresses that occur and the value of the decrease that occurs in ballast using mortar foam. From the results of the analysis of this study, it was found that there was an increase in the ability of ballast with mortar foam material compared to granular material, the decrease in stress that occurred and a decrease in the deformation value in railroad construction gave an option to use conventional ballast substitutes.